PENGARUH KELENGKAPAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO BANGUNAN JHRD BAROKAH - Suryanisari, Pipin; Yusuf, Muhamad (Universitas La Tansa Mashiro, 2023)
This research is based on the number of similar businesses that offer products to consumers so that companies must be able to identify consumer needs in order to compete with copetitors. This study aims to test productcompleteness and price either partially or simultaneously on consumer purchasing decisions at the JHRD Barokah Building Store. The population used is the consumer of the JHRD Barokah Building Shop and a sample of 90 respondents is obtained using the slovin formula. This study uses validity and reliability of a research indicator. This study uses multiple linear regression analysis with SPSS v.25. The results of the analysis carried out show that partially the completeness of the product has a positive and significant effect on Purchase Decisions, while simultaneously Product Completeness and Price have an influence on Purchase Decisions..